Model Struktural Ethnic Entrepreneurship Di Kota Semarang - (Jurusan Administrasi Bisnis Politeknik Negeri Semarang), Andi Setiawan (Teknis, 2015)
There have been many studies that claim the existence of Ethnic Entrepreneurship is very significant influence on the improvement of public welfare. Not a few Migrant Entrepreneurs who become successful and there is also a failure in the city of Semarang. Therefore, the issue of the proposed research is to determine the factors most influential in shaping entrepreneurs who excel in line with expectations. Further variables and indicators of research is also based on previous studies. A model has been developed and five hypotheses have been formulated to address the problem of this research. Data analysis tool used is Structural Equation Modeling (SEM) at 22.0 AMOS program. Research which will be tested in the five objectives of this research. The final result of this research that the findings of the research will be the most dominant variable in influencing the entrepreneurial orientation of the model to be superior entrepreneur is a potential factor. In addition 4 of 5 hypothesis proposed in this research study is acceptable significantly. Suggestions focus on developing entrepreneurial potential factor in its own self.Keywords: Environmental Factors, Motivational Factors, Potential Factor, Entrepreneurial Orientation and Entrepreneurial success